An Argument for Uniqueness About Evidential Support. Issue 1 (October 2016) - Dogramaci, Sinan; Horowitz, Sophie
Abstract: White, Christensen, and Feldman have recently endorsed uniqueness, the thesis that given the same total evidence, two rational subjects cannot hold different views. Kelly, Schoenfield, and Meacham argue that White and others have at best only supported the weaker, merely intrapersonal view that, given the total evidence, there are no two views which a single rational agent could take. Here, we give a new argument for uniqueness, an argument with deliberate focus on the interpersonal element of the thesis. Our argument is that the best explanation of the value of promoting rationality is an explanation that entails uniqueness.